Wounded heroes : vulnerability as a virtue in ancient Greek literature and philosophy - McCoy, Marina, 1968- (Oxford : Oxford University Press, 2014)
McCoy examines how Greek epic, tragedy, and philosophy offer important insights into the nature of human vulnerability especially how Greek thought extols the recognition and proper acceptance of vulnerability. Beginning with the literary works of Homer and Sophocles, she also expands her analysis to the philosophical works of Plato and Aristotle.
Specialized.
Description based on online resource; title from home page (viewed on November 5, 2013).
Keywords: Greek literature -- History and criticism; Vulnerability (Personality trait); Philosophy, Ancient; Virtues in literature